1994
DOI: 10.1111/j.1600-051x.1994.tb01167.x
|View full text |Cite
|
Sign up to set email alerts
|

Trypsin‐like activity levels of Treponema denticola and Porphyromonas gingivalis in adults with periodontitis

Abstract: Treponema denticola (Td) and Porphyromonas gingivalis (Pg) are associated with human moderate and severe adult periodontal diseases. This study quantifies these two anaerobes and their trypsin-like (TL) activities in subgingival plaque collected from both clinically healthy and periodontally diseased sites of human periodontitis patients. Antigen levels of the microorganisms were determined by monoclonal antibodies and TL activities were measured by the fluorescent substrate Z-gly-gly-arg-AFC in a disc format.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 28 publications
0
13
0
Order By: Relevance
“…Proteolytic activity, in particular ‘trypsin‐like’ proteolytic activity of subgingival plaque has been positively correlated with clinical parameters of periodontitis (198, 268, 304). The four pathogens discussed in this review that have been highly associated with periodontitis all produce extracellular proteolytic activity including ‘trypsin‐like’ protelytic activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proteolytic activity, in particular ‘trypsin‐like’ proteolytic activity of subgingival plaque has been positively correlated with clinical parameters of periodontitis (198, 268, 304). The four pathogens discussed in this review that have been highly associated with periodontitis all produce extracellular proteolytic activity including ‘trypsin‐like’ protelytic activity.…”
Section: Discussionmentioning
confidence: 99%
“…Proteolytic activity in subgingival plaque, in particular trypsin‐like proteolytic activity, has been highly correlated with clinical measurements of periodontitis (198, 268, 304). Culture supenatants of A. actinomycetemcomitans Y4 (serotype b) have been shown to have high trypsin‐like proteolytic activity (369).…”
Section: Actinobacillus Actinomycetemcomitans Antigensmentioning
confidence: 99%
“…There was a close relationship between this peptidase activity and attachment loss within a 12-month period (336). The ability of plaque samples to hydrolyze the fluorescent substrate Z-Gly-Gly-Arg-AFC was significantly correlated with the levels of T. denticola and P. gingivalis in plaque samples, as measured by a quantitative monoclonal antibody assay (223).…”
Section: Enzyme Assaysmentioning
confidence: 95%
“…denticola is almost always found in association with other oral micro-organisms, including recognized periodontal pathogens (Faveri et al, 2009;Söder et al, 1993). T. denticola has been shown to coaggregate with a number of these micro-organisms (Grenier, 1992;Onagawa et al, 1994;Yao et al, 1996;Kolenbrander et al, 1995) and, in particular, there seems to be a strong link between P. gingivalis and T. denticola in subgingival plaque samples (Pederson et al, 1994;Simonson et al, 1992). It has been suggested that the occurrence of T. denticola at a site of periodontitis might in fact depend upon the presence of P. gingivalis .…”
Section: Introductionmentioning
confidence: 99%